The negative impact of levothyroxine treatment on urinary luteinizing hormone measurements in pediatric patients with thyroid disease - Demir, And; Böber, Ece; Darcan, Sükran; Aydın, Adem; Stenman, Ulf-Håkan; Büyükgebiz, Atilla; Hero, Matti (Frontiers in Endocrinology, 2023)
Objectives Previous studies suggest urinary luteinizing hormone (LH) and follicle-stimulating hormone (FSH) measurements by immunofluorometric assays (IFMA) as noninvasive alternatives to serum assays for puberty assessment. However, these studies excluded patients with other endocrine disorders and those taking medications. Besides, the recent discontinuation of IFMA manufacturing is a concern. We explored the utility of luminometric assays (LIA) for urinary gonadotropins and thyroid-stimulating hormone (TSH) determinations in euthyroid patients with thyroid pathologies. Methods We used LIA and IFMA assays to measure serum and first-morning-voided (FMV) urine LH, FSH, and TSH concentrations in euthyroid patients with various thyroid disorders. Of the 47 euthyroid patients with normal serum TSH (S-TSH) levels, 14 were receiving levothyroxine therapy. Results FMV total urinary LH (U-LH) concentrations correlated significantly with those measured in serum using either LIA (r=0.67, P<.001) or IFMA (r=0.83, P=.003) in patients not receiving levothyroxine treatment; however, no significant correlation could be detected in patients receiving levothyroxine regardless of the assay method (for LIA: r=0.50, P=.08 and IFMA r=0.44, P=.15). Urinary TSH (U-TSH) concentrations correlated poorly with those in serum in both the untreated and the treated groups (r=-0.13, P=.49, and r=-0.45, P=.11, respectively). Conclusion FMV total U-LH determinations by LIA can be used to assess pubertal development in patients with thyroid pathology, provided the euthyroid patient is not on levothyroxine treatment. U-TSH measurements by LIA cannot replace invasive S-TSH measurements at least in patients with normal S-TSH levels. Further research may reveal the utility of U-TSH determinations in patients with elevated S-TSH levels.